Memahami Pola Resolusi Konflik Kepentingan di Indonesia - Pandu Prasojo (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
When it comes to conflicts that occur massively on a global scale, there is no end in sight. Conflict triggers can start from differences in views, cultures, religions and perceptions that can be the beginning of conflict sparks. In every conflict, of course, there are various interests that drive the conflict. Conflicts that often occur, can lead to a variety of conclusions that can affect what and how a relationship and the end result of two or more individuals experiencing conflict. This journal focuses on conflicts that occur between people who work in the informal sector, people in the ring of a company development area and people in disadvantaged areas. This journal also tries to interpret how conflict patterns can occur in Southeast Asian regions such as Thailand and the Philippines. understanding what, why and how conflict can arise and then develop over time, understanding how conflict can be a pioneer in social change and how conflict resolution occurs. This journal uses a method of writing using in-depth literature studies that depart from books and issues that rise to the surface. This journal finds one conclusion that the pattern of conflict of interest is always repeated and often occurs in developing countries. This is due to the forms of conflict drivers with the same pattern and always occur in society, resulting in the escalation of conflict.